2005
DOI: 10.1088/1742-6596/24/1/008
|View full text |Cite
|
Sign up to set email alerts
|

Lorentz violating electrodynamics

Abstract: After summarizing the most interesting results in the calculation of synchrotron radiation in the Myers-Pospelov effective model for Lorentz invariance violating (LIV) electrodynamics, we present a general unified way of describing the radiation regime of LIV electrodynamics which include the following three different models : Gambini-Pullin, Ellis et al. and Myers-Pospelov. Such unification reduces to the standard approach of radiation in a dispersive and absortive (in general) medium with a given index of re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Some preliminary work along these directions have already been presented in Ref. [14]. We also discuss the implications of reality and causality in the field propagation, applying them to some specific cases already considered in the literature.…”
Section: Introductionmentioning
confidence: 92%
“…Some preliminary work along these directions have already been presented in Ref. [14]. We also discuss the implications of reality and causality in the field propagation, applying them to some specific cases already considered in the literature.…”
Section: Introductionmentioning
confidence: 92%
“…For a discussion of synchrotron radiation in other models with Planck suppressed dispersion corrections see[128] 29. It has recently been suggested that Lorentz violation might play a role in the formation of the pulsar itself, specifically in large pulsar anomalous velocities[192].…”
mentioning
confidence: 99%
“…A detailed description of synchrotron radiation in this model has been presented in Ref. [69]. Subsequently, an unifying point of view was adopted by describing models with linear and quadratic correction terms in the Lagrangian via constitutive relations in Maxwell equations.…”
Section: Modified Electrodynamicsmentioning
confidence: 99%
“…Finally we mention the use of astrophysical phenomena to discuss such modified theories. Distinguished examples are the bounds imposed by polarization measurements from astrophysical sources [43], the study of ultra high energy physics processes, among them cosmic rays, [44,45,46,48,49] and the consequences of the detected synchrotron radiation from the Crab nebulae, as well as that from other objects [21,22,69]. For recent reviews about such topics see Ref.…”
Section: Introductionmentioning
confidence: 99%